The effect of double impact on hygrothermally aged carbon epoxy laminates - Mokhtar , Hanan; Sicot, Olivier; Rousseau, Jerome; Aminanda, Yulfian; Aivazzadeh, Shahram (2012)
This paper studies the effects of a repetitive occurence of impact in the same zone or point. Such occurence is unavoidable as such accidents happen and does not occur directly after the first incident but over a period of time. In order to study the effect, three stratifications of carbon epoxy fibre composite are fabricated and aged under the condition of 70°C at a relative humidity of 85% in a climatic chamber up to 2100h. The three stratifications include the classical sequence of layups used in the industry and two sequences with quasiisotropic /quasi-homogeneous properties. The difference between the two quasi-isotropic/quasi-homogeneous stratification is that one include fibre orientations of ±45° other than 0° and 90°, whereas the other includes fibre orientaions of ±60°. The moisture uptake is noted by taking the weight at regular intervals, using a high precision weight balance, up to saturation state. The first impact test is carried out with the impact energy of 20J and the damage due to impact is assessed using ultrasonic C-scan. The second impact test is carried out under the same conditions after the impacted specimen undergoes a second ageing phase under the same condition with the accumulated ageing period of 2300h. The damage to impact is then assessed again via ultrasonic C-scan to observe the effect of double impact on the carbon epoxy composite. The effects of damage is compared to see the changes in total damage area due to the first and second impact.